Criação de um bloco virtual padrão de cargas para avaliação de fadiga do veículo, isodano com provas experimentais de durabilidade para chassis e carrocerias - Marco Túlio Batista dos Anjos (2019)
This work aims to propose a virtual fatigue block, which consists of virtual tracks and maneuvers and their respective repetitions, standardized, for designing chassis components and bodies in the virtual phases. Using four projects already consolidated, their respective vRLDA (Finite Element based) models were built to provide loads in time histories. In addition, virtual tracks and maneuvers were used which best represent the experimental bench fatigue tests and the LDS which assess the durability of chassis and bodies respectively. From the Level Crossings graphs resulting from the virtual time histories, the resulting wheel center loads in the three main directions of the vehicle from the virtual tracks and static maneuvers with the loads predicted in the experimental tests were compared. After validating the virtual models' way of passing, regarding speed and pathways, a number of repetitions for these pathways and virtual static maneuvers were elaborated so that the virtual accumulated damage was considered equivalent to those predicted in the experimental tests according to the adopted criterion. Comparison results of virtual vertical and longitudinal load magnitudes when compared with LDS results and longitudinal bench tests show considerable discrepancies due to PotHole. However, such discrepancies were considered acceptable, mainly because LDS also results in noticeably shifting loads (as discussed in Annex A). For lateral loads, there were no differences like the other two previous directions. Finally, calculated the number of repetitions for each static maneuver and virtual track, with the equivalent damage criterion adopted, the accumulated of the virtual fatigue schedule proposed respected the criterion intervals after being properly adjusted and thus considered viable for virtual durability vehicle evaluation.